Regional Sector Priority Index: A Composite Approach for Economic Sector Prioritization in South Sumatra Province - Wan Ruslan Abdul Ghani (Penerbit Goodwood, 2026)
Purpose: This study develops the Regional Sector Priority Index (RSPI), a composite instrument integrating the Index of Forward Linkage (IFL), Index of Backward Linkage (IBL), and Output Index (OI) within the Interregional Input-Output (IRIO) framework to identify and rank priority economic sectors in South Sumatra, Indonesia.Research Methodology: A quantitative descriptive-explanatory approach was employed using secondary data from the 2016 Indonesian IRIO Table covering 52 economic sectors. The analysis proceeds through the technology coefficient matrix, the Leontief inverse, and the sequential calculation of IFL, IBL, and OI, which are expressed relative to their cross-sector means and aggregated with equal weights. Robustness was evaluated under four weighting scenarios: baseline, forward-oriented, backward-oriented, and output-oriented.Results: Coal and Lignite Mining ranked first (RSPI = 8.725), followed by Oil, Gas and Geothermal Mining, Electricity, Coal and Oil and Gas Refining, and the Chemical and Pharmaceutical Industry. Of 52 sectors, 12 were Strategic Leading Sectors, 23 High Priority Sectors, and 17 Supporting Sectors. The top-ten ranking remained stable across all scenarios.Limitations: The analysis relies on the 2016 IRIO Table and does not fully reflect post-pandemic structural changes or the ongoing energy transition.Conclusions: South Sumatra's economy remains dominated by energy and resource-based industries with strong intersectoral linkages. The RSPI offers a more comprehensive tool for priority-sector identification than single-indicator approaches. Contributions: This study introduces the RSPI as a novel, replicable composite index for evidence-based regional development planning in Indonesian provinces.